The Effects of Role Overload and Resilience on Psychological Well-Being Among the Sandwich Generation in Bandung - Wines Restu Alina; Rifqi Farisan Akbar; Prinska Damara Sastri (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study investigates the extent to which role overload and resilience explain psychological well-being among the sandwich generation in Bandung. The research used a quantitative approach, involving 115 employed Generation Z respondents aged 20–29 years residing in Bandung. Data were collected through a structured questionnaire and analyzed using multiple linear regression. The results reveal that role overload and resilience jointly have a significant influence on psychological well-being, accounting for 80.7% of the explanatory contribution. The partial analysis shows that role overload has a negative but non-significant effect on psychological well-being (p > 0.05). Conversely, resilience demonstrates a positive and significant effect and becomes the strongest predictor in the model (p < 0.05). These findings indicate that psychological well-being among the sandwich generation is influenced more strongly by internal adaptive capacity, particularly the ability to withstand pressure, adjust to difficult situations, and recover from stress, than by the perceived intensity of multiple role demands